(3eNJUQ bjGe Gddjds - (3Jbi GdOjf GdebQjRis; (3GdeQhRj , eMeO Hf fUQ GdeQhRj, CHh YHO Gddg,J (B294 (3g` s
(3ChdgG (B:s
(3jHOC HPcQ GdJQZjH ai bjGe Gddjd ef cJGH Gddg YR hLd s
(3BNQgG (B:s
(3jfJgi HHGH ef bfJ GdSfI cdgG EdG GdfUa GdChd ef QeVGf s
(3GdfSNI HgG MhGTs
(3HChdg agQS HNW MOjK LOkGs
(3ef GdhQbI (B132 (3JbjjOGJ TJi HNW GdeDda ai ehVhYGJ CNQis
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdJUha hGdBOGH GdTQYjIs